Varicella - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur